Development of Vocabulary in English in Young Learners with Kinesthetic Learning Style - Pokorná, Linda (Univerzita Pardubice, 2018)
This bachelor thesis is interested in the development of vocabulary of English language in young learners with kinesthetic learning style. The basic terms such as young learners, vocabulary, learning style, and kinesthetic learning style are defined. On the basis of the theoretical part, criteria for teaching vocabulary to young learners with kinesthetic learning style are created. According to these criteria, nine activities developing English vocabulary in kinesthetic young learners are suggested. They can be found in the appendices. In empirical part, it is described which criteria and how are fulfilled in every activity.
Rozvoj slovní zásoby v anglickém jazyce u žáků na I. stupni ZŠ s kinestetickým učebním stylem
Keywords: žáci mladšího školního věku; slovní zásoba; styly učení; kinestetický učební styl; young learners; vocabulary; learning styles; kinesthetic learning style